Analisis Gaya Kepemimpinan Perspektif Ekonomi Islam dalam Meningkatkan Kinerja Karyawan : (Studi Pada PT Mitra Bumdes Bersama Sliyeg Indramayu) - Casriyanti Casriyanti; Samrokim Samrokim (LPPM STAIS Dharma Indramayu, 2022)
One of the factors of organizational success is leadership style. However, there are still leadership styles that are not fully in accordance with leadership based on an Islamic Economic Perspective, such as at PT Bumdes Bersama Sliyeg Indramayu, namely leadership that is not fully firm towards employees so that it can reduce employee performance, especially in decision making, communicating and providing compensation. The formulation of the problem in this research includes, How has the leadership style changed at PT Bumdes Bersama Sliyeg Indramayu and its impact on the performance of Kurnia Walet employees from an Islamic Economics Perspective? The type of research used is field research. The approach used is qualitative research. This research was conducted at PT Bumdes Bersama Sliyeg Indramayu using data collection techniques in the form of observation, interviews and documentation. The results of the research show that the leadership style of the previous leader Kurnia Walet was less appropriate in terms of decision making due to his lack of firmness towards employees. As well as not supervising its employees, tact in communication still needs to be improved in conveying messages. in relation to leadership in providing compensation in the form of salary or wages and THR during Eid but it does not meet the decent principle because the salary is not in accordance with the minimum wage limit of the Ponorogo City government. Meanwhile, the current leadership style of the Leader of PT Bumdes Bersama Sliyeg Indramayu in supervising, directing, making decisions, communicating, finding solutions and controlling employee performance is much better than before, but there are still things that need to be improved, namely in terms of providing wages or rewards. given by the leader is considered unfair by the employees, the reward system is considered unfair according to the employees' perception.